Physiotherapy in Telerehabilitation Mode Improves HealthRelated Quality of Life and Functional Muscle Strength in COVID 19 Survivors: A Case Series (Indian Journal of Physiotherapy and Occupational Therapy - An International Journal, 2020)
Introduction: Pulmonary rehab is effective for various chronic lung conditions. COVID-19 leads toconditions like ARDS, SARI wherein pulmonary rehab has been shown to be effective. Under the currentpandemic situation, wherein access to transport and healthcare facilities have been difficult, ReLivaPhysiotherapy & Rehab initiated tele-pulmonary rehab for COVID patients, known as” Respirehab”. Thisarticle is to present findings of the patients who have completed the 1-month Respirehab program.Objective:To determine whether respirehab delivered to COVID-19 patients has beneficial effects pre andpost1. Functional outcome measures2. Clinical outcome measures.Materials & Method: Respirehab is a 1-month program delivered online through real time video calls andexercise prescription through pre-recorded videos. Key components are breathing exercises and progressivephysical exercises. This program starts with a detailed assessment on a video call with a physiotherapist,subsequent to which a plan of care is prepared online. Weekly reviews conducted and accordingly treatmentprotocols were modified, whenever required. It was ensured that at least 2 live video sessions per week wereheld with the patient for motivation and program safety. The patients’ outcomes were measured on SGRQ,MMRC, 1 RM – 10 RM, and SPO2 data. We collected these data in the beginning of the program and at aweekly interval.Results: Patients showed improvement on each of the scales and which was significant. The pre and postdata was analysed using following outcome measures SGRQ, MMRC, 1RM-10RM, SPO2 MONITORING.The average improvement seen in the outcomes is 70%.Conclusion: Respirehab holds a lot of assurances for patients recovering from COVID-19. In the currentsample size, all patients showed improvement in clinical and functional outcomes. Findings from a largersample will validate the benefits more conclusively.
Keywords: COVID rehabilitation, COPD, ARDS, COVID-19, SGRQ, MMRC, TELEREHABILITATION, Respirehab.